The causal relationship between gut microbiota and diabetic neuropathy: a bi-directional two-sample Mendelian randomization study - Xie, Long; Gan, Wen; Cai, GuangRong (Frontiers in Endocrinology, 2024)
Background: Many studies suggest a strong correlation between gut microbiota (GM) and diabetic neuropathy (DN). However, the precise causal relationship between GM and DN has yet to be fully elucidated.Hence, a bi-directional Mendelian randomization (MR) analysis was used to examine the association between GM and DN.Methods: Widely known genome-wide association study (GWAS) of GM was collected from the MiBio Gen project. Summary-level datasets for DN were taken from the FinnGen project. Inverse variance weighted approach was used for evaluating the causal relationship between GM and DN.Subsequently, pleiotropy and heterogeneity tests were performed to verify the reliability of the data. Furthermore, a bidirectional two-sample MR analysis was done to investigate the directionality of the causal relationships. Gene Ontology analysis was conducted to identify the associations that could indicate biological functions.We identified potential causal associations between GM and DN (p < 0.05 in all three MR methods). Among them, we found increased levels of Christensenellaceae R-7 (Odds ratio, OR= 1.52; 95% confidence interval, CI = 1.03-2.23; p = 0.03), Ruminococcaceae UCG013 (OR =1.35; 95% CI = 1.00-1.85; p = 0.04), and Eggerthella groups (OR = 1.27; 95% CI = 1.05-1.55; p = 0.01), which may be associated with a higher risk of DN, while increased levels of Peptococcaceae (OR = 0.69; 95% CI = 0.54-0.90; p < 0.01) and Eubacterium coprostanoligenes groups (OR = 0.68; 95% CI = 0.49-0.93; p = 0.01) could be associated with a lower risk. Gene Ontology pathway analysis revealed enrichment of genes regulated by the associated single-nucleotide polymorphisms (SNPs) in the apical plasma membrane, glycosyltransferase activity, hexosyltransferase activity and membrane raft. Reverse MR analyses indicated that DN was associated with five microbial taxa in all three MR methods.The results of our study validate the possible causative relationship between GM and DN. This discovery gives new perspectives into the mechanism on how GM influences DN, and establishes a theoretical foundation for future investigations into targeted preventive measures.